1997
DOI: 10.1007/s11606-006-5001-0
|View full text |Cite
|
Sign up to set email alerts
|

Presentations of Acute Myocardial Infarction in Men and Women

Abstract: OBJECTIVE:To assess the influence of gender on the likelihood of acute myocardial infarction (AMI) among emergency department (ED) patients with symptoms suggestive of acute cardiac ischemia, and to determine whether any specific presenting signs or symptoms are associated more strongly with AMI in women than in men. DESIGN:Analysis of cohort data from a prospective clinical trial. SETTING:Emergency departments of 10 hospitals of varying sizes and types in the United States. PATIENTS:Patients 30 years of age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(21 citation statements)
references
References 35 publications
4
16
1
Order By: Relevance
“…As expected and largely described,10 11 their mortality tended to be higher (18.10% vs 10.65%; p<0.063) as forecast by higher values of GRACE. However, compared to men, they have not shown evidence of differences as far as triage was concerned.…”
Section: Discussionsupporting
confidence: 79%
“…As expected and largely described,10 11 their mortality tended to be higher (18.10% vs 10.65%; p<0.063) as forecast by higher values of GRACE. However, compared to men, they have not shown evidence of differences as far as triage was concerned.…”
Section: Discussionsupporting
confidence: 79%
“…These results are similar to those observed in the WHAS (2005) where female patients were more likely to suffer from diabetes mellitus, hypertension, stroke, and CHF; however, no significant difference was found in other comorbidities [12]. In a similar way, Zucker et al (1997) found women to be more likely to suffer from diabetes mellitus (25%) and hypertension (55%) when compared to men [14]. Nedkoff et al (2015) also found women to have a higher prevalence of comorbid conditions such as diabetes mellitus, hypertension, and CHF [13].…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, Zucker et al (1997) observed no difference between gender in STEMI likelihood, but report a higher number of men with ST elevations as compared to women (OR: 1.9; CI: 1.5 - 2.3). Therefore, the gender interaction showed an increase in likelihood of women with ST elevations rather than without [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Though our analysis does not reveal why women were more likely to be delayed, previous research suggests a plausible explanation: symptom presentation in women with cardiac disease differs from that of men18 and a coronary event may not be recognized as readily by the patient19 or by EMS personnel. Inappropriate delays may occur because there is less certainty of cardiac involvement, because more time is spent diagnosing the condition, because the patient’s condition may not be seen as emergent, or as the result of some combination of these factors.…”
Section: Discussioncontrasting
confidence: 67%